A peptide affinity reagent for isolating an intact and catalytically active multi-protein complex from mammalian cells. Issue 5 (1st March 2015) - Saathoff, Hinnerk; Brofelth, Mattias; Trinh, Anne; Parker, Benjamin L.; Ryan, Daniel P.; Low, Jason K.K.; Webb, Sarah R.; Silva, Ana P.G.; Mackay, Joel P.; Shepherd, Nicholas E.
Graphical abstract: Abstract: We have developed an approach for directly isolating an intact multi-protein chromatin remodeling complex from mammalian cell extracts using synthetic peptide affinity reagent4 . FOG1(1–15), a short peptide sequence known to target subunits of the nucleosome remodeling and deacetylase (NuRD) complex, was joined via a 35-atom hydrophilic linker to the StreptagII peptide. Loading this peptide onto Streptactin beads enabled capture of the intact NuRD complex from MEL cell nuclear extract. Gentle biotin elution yielded the desired intact complex free of significant contaminants and in a form that was catalytically competent in a nucleosome remodeling assay. The efficiency of4 in isolating the NuRD complex was comparable to other reported methods utilising recombinantly produced GST–FOG1(1–45).